KEABSAHAN PENYANDERAAN (GIJZELING) WAJIB PAJAK BERITIKAD BAIK (CONTOH KASUS: PUTUSAN PENGADILAN PAJAK NOMOR: 72329/PP/M.XVIIIA/99/2016) - arnetta anggrainie santoso; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
Taxes are mandatory contributions that must be paid by every citizen to the State. In the implementation of tax collection, tax is coercive and can be enforced, this is because the role of taxes as a source of state revenue, especially Indonesia, which is 75% of the source of income comes from the tax sector, thus the contribution of society as a tax bearer in terms of obeying tax payments is expected because with this contribution it can help or equal to providing support to the State to achieve the country's goals, namely one of which is to carry out national development and this development is carried out evenly throughout the territory of the country. How is the legality of the hostage-taking (gijzeling) of good faith taxpayers not contradicting Article 33 paragraph (1) of Law Number 19 Year 1997 concerning Tax Collection by Force Letter as amended by Law Number 19 Year 2000 concerning Amendments to Law Number 19 of 1997 concerning Tax Collection with a Warrant ?. This type of research uses the Normative Law research method, the research specification used is descriptive analytical, the type of data used in this study is secondary data, the data collection techniques used by the author are document studies or literature to collect secondary data. In this study, the authors used qualitative data analysis technique